PENERAPAN KONSEP PEWARNAAN GRAF DALAM PENYUSUNAN JADWAL KBM MENGGUNAKAN METODE WELCH-POWELL DENGAN PEMROGRAMAN VBA MACRO EXCEL - Faturahman Faturahman; Amrullah Amrullah; Laila Hayati; Sudi Prayitno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
The problem of scheduling of teaching and learning at SMKN 5 Mataram was ainteresting problem. On the problem, there were the teachers who teach the same subject at the same time in several different classes. The problem will be solving by the graph coloring concept. Base on the data of scheduling, we obtain the adjecency matrix with size 195 × 195. We use the Welch-Powell algorithm to get the number of coloring graph. By the implentation VBA Macro Excel programming of the algorthm, we obtain the upper bound the number coloring is 5. So, by the upper bound we can design a scheduling without the problen which the teacher who teach the same subject at the same time in several different classes.